2018
DOI: 10.1186/s12870-018-1563-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen topdressing timing modifies free amino acids profiles and storage protein gene expression in wheat grain

Abstract: BackgroundNitrogen is one basic element of amino acids and grain protein in wheat. In field experiments, wheat plants were subjected to different timing of nitrogen topdressing treatments: at the stages of emergence of the top fifth leaf (TL5), top third leaf (TL3) and top first leaf (TL1) to test the regulatory effects of nitrogen topdressing timing on grain protein quality. The underlying mechanisms were elucidated by clarifying the relationship between proteolysis in vegetative organs and accumulation of am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…Overexpression of the AlaAT gene significantly increases the grain nitrogen use efficiency [16]. Higher expression levels of cysteine and thiol proteases indicate the strong degradation and mobilization of soluble proteins in the leaves [11]. In the present study, the expression levels of TaGS (TaGS1 and TaGS2) and TaAlaAT were higher in HMW-D1p than HMW-D1a, and this was also the case for the genes encoding cysteine and thiol proteases ( Figure 6).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Overexpression of the AlaAT gene significantly increases the grain nitrogen use efficiency [16]. Higher expression levels of cysteine and thiol proteases indicate the strong degradation and mobilization of soluble proteins in the leaves [11]. In the present study, the expression levels of TaGS (TaGS1 and TaGS2) and TaAlaAT were higher in HMW-D1p than HMW-D1a, and this was also the case for the genes encoding cysteine and thiol proteases ( Figure 6).…”
Section: Discussionsupporting
confidence: 67%
“…PPIase facilitates the accumulation of protein polymers with the assistance of SUMO1 [21]. The expression of PDI catalyzes the formation of disulfide bonds, which are positively correlated with protein polymer formation [11,22]. In the present study, the expression levels of TaPPIase, TaSUMO1, and TaPDIL2-1 were higher in HMW-D1p than HMW-D1a ( Figure 7E-G), and the maximum TaPDIL2-1 expression level occurred earlier in HMW-D1p, thereby suggesting that larger protein polymers were formed in HMW-D1p, as demonstrated by the accumulation of PBs and GMP, and the concentration of disulfide bonds ( Figure 1A, Figure 2E, and Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cui et al (2010) demonstrated the achievability of maximized wheat yield and minimized environmental risks through the adjustment of the N fertilization proportions between seasons. Likewise, others also successfully improved crop yield, NUE, and grain quality by integrating the N fertilization amount and topdressing timing (Liu et al 2019b;Qu et al 2018;Zhong et al 2018). In other plants rather than food crops, the benefits of topdressing or controlreleased N fertilization on plant growth and productivity have been similarly reported in Platycodon grandiflorum (Zhu and Zhang 2017), Cleome gynandra (Mavengahama 2013), and Glycine max (Zhou et al 2019a).…”
Section: Introductionmentioning
confidence: 90%